A New Type of National Character as Depicted in M. Magauin’s Novel «Sary Kazakh» - Takhan, Серик (Turkic Studies Journal, 2021)
The article examines the national type of consciousness as manifested in the protagonist of M. Magauin’s novel «SaryKazakh». This type of positive hero’s novelty is determined as closely associated with the character reflecting the philosophy of the Kazakh people’s history. Throughout the character’s formation the author depicts in a real contemporary social space the restoration of the Kazakh people’s broken spiritual ties with the past centuries’ cultural and historical traditions. The national character is revealed in the depicted conflicts and in the correlations of his actions and thoughts with the realities and phenomena of national social life over a large historical span. With the novel’s whole structure and plot composition, the writer confidently proves that the dialectic of this fictional historical person’s character is logical and convinces us fully that the depicted is possible, aligning his aesthetic ideal with the historical tasks facing contemporary Kazakhstani society.